Agonist-dependence of functional properties for common nonsynonymous variants of human transient receptor potential vanilloid 1. Issue 7 (July 2016) - Wang, Sen; Joseph, John; Diatchenko, Luda; Ro, Jin Y.; Chung, Man-Kyo
Abstract : Abstract: Transient receptor potential vanilloid 1 (TRPV1) is a polymodal receptor activated by capsaicin, heat, and acid, which plays critical roles in thermosensation and pain. In addition, TRPV1 also contributes to multiple pathophysiological states in respiratory, cardiovascular, metabolic, and renal systems. These contributions are further supported by evidence that variations in the human TRPV1 (hTRPV1) gene are associated with various physiological and pathological phenotypes. However, it is not well understood how the variations in hTRPV1 affect channel functions. In this study, we examined functional consequences of amino acid variations of hTRPV1 induced by 5 nonsynonymous single-nucleotide polymorphisms (SNPs) that most commonly exist in the human population. Using electrophysiological assays in HEK293 cells, we examined 9 parameters: activation, Ca 2+ permeation, and desensitization after activation by capsaicin, acid, and heat. Our results demonstrated that the 5 SNPs differentially affected functional properties of hTRPV1 in an agonist-dependent manner. Based upon the directionality of change of each phenotype and cumulative changes in each SNP, we classified the 5 SNPs into 3 presumptive functional categories: gain of function (hTRPV1 Q85R, P91S, and T469I), loss of function (I585V), and mixed (M315I). These results reveal a spectrum of functional variation among common hTRPV1 polymorphisms in humans and may aid mechanistic interpretation of phenotypes associated with nonsynonymous hTRPV1 SNPs under pathophysiological conditions. Abstract : Five common nonsynonymous variants of TRPV1 show differential activation, permeation, and desensitization in an agonist-dependent manner.